Comparison of deltoid ligament repair and non-repair in acute ankle fracture: A meta-analysis of comparative studies. - Wenxuan Guo (Public Library of Science (PLoS), 2021)
Background Rupture of the deltoid ligament (DL) in acute ankle fracture is very common. However, there is still insufficient evidence on whether to repair the DL in acute ankle fracture. Therefore, a systematic review and meta-analysis of comparative studies was performed to report the outcome of DL repair in acute ankle fracture. Methods The PubMed, Cochrane Library, EMBASE and Web of Science databases were searched from the inception dates to October 31, 2020, for comparative studies. The methodological quality was evaluated based on the risk-of-bias tool of the Cochrane Collaboration for Randomized Controlled Trials (RCTs) or the Risk-of-Bias Assessment Tool for Non-randomized Studies (RoBANS). The post-operative medial clear space (MCS), final MCS, American Orthopaedic Foot and Ankle Society (AOFAS) ankle-hindfoot score, visual analogue scale (VAS) score and incidence of complications were analysed. Results A total of 8 comparative studies involving 388 participants who suffered Weber type B or C ankle fractures were included in this meta-analysis. The results showed that the post-operative MCS, final MCS, AOFAS score and rate of complications were statistically superior in the DL repair group. For the VAS score, there was no significant difference between the DL repair group and the DL non-repair group. Conclusions In this meta-analysis of comparative studies, DL repair offered great advantages in terms of the post-operative MCS, final MCS, AOFAS score and rate of complications compared with non-repair. The repair of the DL in patients with acute ankle fractures might be beneficial to ankle joint stability and assist in improving the quality of ankle reduction. More high-quality and prospective studies with long follow-up durations are needed to further demonstrate the superiority of DL repair over non-repair.